Accountability and Supervision in Guidance and Counseling: Issues and Solutions - Apriliana, Yona; N, Neviyarni; Syukur, Yarmis (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Accountability and supervision are two essential aspects in the implementation of Guidance and Counseling (GC) services in schools. Both function to ensure that all GC activities are carried out effectively, efficiently, and in accordance with professional standards. Research and literature indicate that accountability in GC includes counselors’ responsibility for program implementation, the use of resources, and the outcomes of services provided to students and stakeholders. Meanwhile, supervision serves as a control and developmental mechanism that ensures the delivery of services aligns with ethical codes and educational goals. However, the implementation of accountability and supervision in the field still faces various challenges, such as low awareness of their importance, lack of structured supervision, and limited supporting facilities. To address these issues, it is necessary to strengthen counselors’ competencies, improve data-based monitoring systems, and enhance sustainable institutional support. By consistently applying the principles of accountability and supervision, GC services in schools can become more transparent, professional, and positively impactful on students’ development.